In Vitro Regeneration of Pimpinella Anisum L. Using Different Plant Growth Regulators - Ghazi, Ansam; Ghani, Fatma H.; Mohsin, Noora M. (Iraqi Journal of Science, 2019)
Plant regeneration protocols were developed for medicinally important anise (Pimpinella anisum L.) that successfully achieved from seeds. Seeds were sterilized and inoculated on Murashige and Skoog (MS) medium with and without gibberellins (GA3) until full germination. The highest percentage of germination (100%) was recorded on MS medium treated with 2.0 mg/L GA3 after 7 days. For shoot proliferation, different concentrations of 6- benzyl adenine BA (1, 1.5, 2 mg/L) were used. To enhance shoot induction, 0.1 mg/L of naphthalene acetic acid (NAA) and 0.01 mg/L of thidiazuron (TDZ) were tested along with BA. Direct regenerated shoots were obtained on MS medium supplemented with BA alone (2mg/L) which gave (7shoot/explant), while the presence of NAA and TDZ at low concentration encourage of somatic embryogenesis. A single stem explant was able to produce 25 micro shoots after (24) days of culture. Rooting was experimented at different levels of NAA (0, 0.5, 1, 1.5 mg/L). The medium that devoided from growth regulator and the media with the lowest level of NAA were the most effective in inducing root. Finally, it was concluded that cytokinins are essential for inducing the direct regeneration and the addition of auxin along with there is necessary for the induction of somatic embryogenesis.